Español de Rosario Estudios sociolinguísticos - DONNI DE MIRANDE, Nélida E. (UNIVERSIDAD NACIONAL DE ROSARIO, 1987)
Otros autores: BORETTI DE MACCHIA, Susana H.; FERRER DE GREGORET, María Cristina; SANCHEZ LANZA, Carmen; MARTINO, Nora